INTERNALISASI PENDIDIKAN KECAKAPAN HIDUP MELALUI LEARNING CYCLE MODEL PADA PEMBELAJARAN PPKn - Rizyanti Rizyanti; Sudjarwo Sudjarwo; Irawan Suntoro (Jurnal Studi Sosial / Journal of Social Studies, 2014)
The purposes of this research were to internalize life skills education through the learning cycle model which can improve students learning outcomes in civics lesson dan apply learning through the learning cycle model for improving students learning outcomes in civics. The research was using classroom action research. Data was analyzed by using descriptive analysis techniques to know the effectiveness of learning through efforts to internalize life skills education as the learning cycle model. Life skills that are the object of this research is focused on personal skills, which are self awareness skills and thinking skills, also social skills which is consist of communication skills and the ability to work together. The results of this research were needs development of internalize life skills education through learning cycle model to increase affective, cognitive, and psychomotor skill of students and learning by internalize life skills education through the learning cycle model can improve learning outcomes of students, so it is effectively used.Penelitian ini bertujuan menginternalisasi pendidikan kecakapan hidup melalui learning cycle model yang dapat meningkatkan hasil belajar siswa pada pelajaran PPKn dan mengaplikasikan pembelajaran melalui learning cycle model untuk meningkatkan hasil belajar pada pembelajaran PPKn. Penelitian menggunakan pendekatan Penelitian Tindakan. Data dianalisis menggunakan teknik analisis deskriptif untuk mengetahui efektifitas pembelajaran melalui learning cycle model sebagai upaya menginternalisasi pendidikan kecakapan hidup. Kecakapan hidup yang menjadi objek penelitian ini difokuskan kepada kecakapan personal yang terdiri atas kecakapan mengenal diri dan kecakapan berfikir serta kecakapan sosial yang terdiri atas kecakapan berkomunikasi dan kecakapan bekerja sama. Hasil penelitian menunjukkan bahwa membutuhkan pembelajaran menggunakan learning cycle model untuk meningkatkan kemampuan kognitif, afektif, dan psikomotor peserta didik dan pembelajaran dengan cara menginternalisasi pendidikan kecakapan hidup melalui learning cycle model dapat meningkatkan hasil belajar peserta didik, sehingga sangat efektif digunakan.Kata kunci: learning cycle, life skill, pendidikan kecakapan hidup